Biosurfactant-producing Rhodococcus ruber TD2 isolated from oil poluted water in vung tau coastal zone - Hien, Lai Thuy; Yen, Nguyen Thi; Nga, Vuong Thi (Academia Journal of Biology, 2013)
Thanks to their advantages compared with other microbial and synthetic surfactants, Rhodococcus biosurfactants are widely studied to apply in new advanced technologies, such as environmental bioremediation, improved polymeric material construction and biomedicine. A biosurfactant-producing strain TD2 was isolated from the oil poluted water at Vung Tau coastal zone. Strain TD2 was observed as rod-shaped, positive gram, non-spore bacterium. The strain was identified as Rhodococcus ruber TD2(100% identity Rhodococcus ruber X 80625) based on 16S rDNA analysis. Investigation of influence of environmental conditions on cell growth and biosurfactant production showed that strain TD2 produced highest biosurfactant at 30oC, pH 8-9, 1-2% NaCl (w/v) and olive oil as carbon source. In this condition, Rhodococcus ruber TD2 exhibited to be a potential producer attaining 94% of emulsifying index E24 and the maximum yield of crude biosurfactant production was 13.7 g/l. GC-MS analysis revealed that biosurfactant of Rhodococcus ruber TD2 was ester of Hexadecenoic acid or Hexanedioic acid bis 2-ethylhexyl containing of many –OH and C=O groups in structural chemicals.